Investigating Associations Between the Diagnostic Specifiers for Binge-Eating Disorder, Other Clinical Features, and the Presence of a High Body Mass Index: A Population-Based Study - Mohammed Mohsin; Malakeh Hamoui; Stella Kozmér; Stephen Touyz; David Currow; Phillipa Hay (Obesities)
Binge eating is the cardinal feature of Binge-Eating Disorder (BED) and is known to be associated with obesity with bidirectional causality. This study aimed to investigate the association of diagnostic specifiers of binge eating, as mandated in the DSM-5 definition of BED, i.e., Criteria B and C (presence of marked distress) and weight/shape overvaluation with body mass index (BMI); and to examine the associations of high BMI with distress, pain, anxiety, and physical and mental health-related quality of life (PHRQoL and MHRQoL). Data for a sub-sample of 255 adults with recurrent binge eating (Criterion A) and without anorexia or bulimia nervosa diagnoses were extracted from the 2017 South Australian Health Omnibus Survey. Bivariate analyses were used to explore the association of DSM-5 BED specifiers with BMI and other measures. This study found that specific BED diagnostic specifiers related to binge eating were associated with higher BMI and distress levels. Additionally, individuals with BED who experience weight/shape overvaluation and higher BMI levels were associated with heigh levels of pain and anxiety, and had poorer PHRQoL and MHRQoL. These findings in relation to the association of higher BMI with different BED specifiers support the clinical significance of the DSM-5 Criterion B and C for BED.